STUDY OF WATER-FLOATING STRUCTURE INTERACTION RESPONSES IN WATER TANK EXCITED BY SEISMIC LOAD AS AN ALTERNATIVE OF SEISMIC ISOLATION SYSTEM - Bagaskoro, Adika
The need for a new land and various disasters that occur in buildings that are supported on the ground make floating structures an alternative solution to solve these problems. In this thesis, we will discuss the interactions that occur between the floating structure and water (hydroelastic interaction) in a water-tank that is excited by several dynamic loads. The structure is modelled as 1D Euler-Bernoulli beam and the fluid modeled follows the Laplace ideal fluid equation. The solution is done using time domain analysis using the predictor-corrector method at each time-step. Numerical calculations of structural, fluid and fluid-structure responses were verified against several literature studies and yielded quite good results. Next, this thesis discuss a comparative analysis of the response of the floating structure to the building that is firmly attached to the ground (fixed-based) will be presented. As a result, the floating structure indicates a dissipation process that occurs in the water medium and the floating structure to produce a better response in terms of roof acceleration and internal forces acting on the base of the building that excited by dynamic loads (earthquake and harmonic loads).